Предмет: Алгебра,
автор: hleb98791
1). Упростить выражение:
а) ( х – 4)(6 х + 7) – 2х( 3х – 5);
б) 2а(а – 3) – ( а – 3)2;
в) ( х + 2)2 – 4х
Ответы
Автор ответа:
0
Ответ: а) -7х - 28; б) а² - 9; в) х² + 4.
Объяснение:
а) (х - 4)(6х + 7) - 2х(3х - 5) = 6х² + 7х - 24х - 28 - 6х² + 10х = -7х - 28;
б) 2а(а - 3) - (а - 3)² = 2а² - 6а - (а² - 6а + 9) = 2а² - 6а - а² + 6а - 9 =
= а² - 9;
в) (х + 2)² - 4х = х² + 4х + 4 - 4х = х² + 4.
Похожие вопросы
Предмет: История,
автор: dosmahanbetaaulym062
Предмет: Українська мова,
автор: eridza2
Предмет: История,
автор: d7917094
Предмет: Математика,
автор: 11Loki10
Предмет: Физкультура и спорт,
автор: melrot555bebe